Atividade in vitro dos óleos essenciais de condimentos frente a Candida glabrata sensíveis e resistenes ao fluconazol - Soares, Isaura Helena (2012)
In the present study, in vitro antifungal activity of essential oils obtained from Origanum vulgare (oregano), Cinnamomum zeylanicum (cinnamon), Lippia graveolens (Mexican oregano), Thymus vulgaris (thyme), Salvia officinalis (sage), Rosmarinus officinalis (rosemary), Ocimum basilicum (basil) e Zingiber officinale (ginger) was assessed against Candida glabrata isolates. A group of 36 fluconazole-susceptible C. glabrata isolates were used and another group, derived from the first, obtained after in vitro induction of the fluconazole-resistance, totalizing 72 isolates tested. The methodology used was broth microdilution, cancentrations of 50 μg/mL, 100 μg/mL, 200 μg/mL, 400 μg/mL, 800 μg/mL, 1600 μg/mL and 3200 μg/mL were used, through which Minimal Inhibitory Concentration (MIC) and Minimal Fungicidal Concentration (MFC) were determined. Thyme, sage, rosemary, basil and ginger essential oils showed no antifungal activity on the tested concentrations. Antimicrobial activity lower than or equal to 3200 μg/mL was observed for oregano, Mexican oregano and cinnamon essential oils, being oregano essential oil the most potent. Oregano essential oil has shown the best antifungal activity against fluconazole-susceptible C. glabrata group. Likely, Mexican oregano essential oil has shown the best antifungal activity against fluconazole-susceptible C. glabrata group. And cinnamon essential oil has shown the best antifungal activity against fluconazole-resistant isolates of C. glabrata.